A polyphasic approach to delineate species in Bipolaris - Chitrabhanu S. Bhunjun (2020)
© 2020, MUSHROOM RESEARCH FOUNDATION. Bipolaris species are important plant pathogens with a worldwide distribution in tropical and temperate environments. Species recognition in Bipolaris has been problematic due to a lack of molecular data from ex-type cultures, the use of few gene regions for species resolution and overlapping morphological characters. In this study, we evaluate the efficiency of different DNA barcodes in species delimitation in Bipolaris by phylogenetic analyses, Automatic Barcode Gap Discovery and Objective Clustering. GAPDH is determined to be the best single marker for the genus. These approaches are used to clarify the taxonomic placement of all sequences currently named as Bipolaris in GenBank based on ITS and GAPDH gene sequence data. In checking various publications, we found that the majority of new host records of fungal species published in the Plant Disease journal from 2010 to 2019 were based on BLAST searches of the ITS sequences and up to 82% of those records could be erroneous. Therefore, relying on BLAST searches from GenBank to name species is not recommended. Editorial boards of journals and reviewers of new record papers should be aware of this problem. In naming Bipolaris species, whether new or known, it is recommended to perform phylogenetic analyses based on GAPDH using the correct taxon sampling for accurate results and the species relationship should have reliable statistical support. At least two new species are represented by molecular data in GenBank and we provide an updated taxonomic revision of Bipolaris. We accept 45 species in Bipolaris and notes are provided for all the species including hosts and geographic distribution.